Type B aortic intramural hematoma - when a sheep becomes a wolf - Coelho,Nuno Henriques (2019)
Introduction: Type B aortic intramural hematoma (B-IMH) has a complex and variable natural history: it can remain stable and resolve spontaneously or progress to dissection, aneurysm, ulcer or even rupture. The possibility of disease progression, frequently with mild or no symptomatology, poses a significant treatment dilemma. Clinical Case: We report a case of a 60 year-old-female diagnosed with an acute B-IMH, initially treated medically. However, 1-month control CTA revealed disease progression (increased B-IMH thickness and evolution to an ulcer-like-projection with 20 mm diameter and 11 mm depth). She was submitted to a left carotid-subclavian bypass followed by TEVAR and left-subclavian ostial embolization. During follow-up (5 months) patient remain asymptomatic, demonstrating favorable aortic remodeling. Conclusion: Type B-IMH is a dynamic pathology. From presentation to late follow-up, patients remain at high risk for abrupt catastrophic complications. As reported, TEVAR seems to be a safe and effective approach in the event of unfavorable evolution.